Budgetary Transparency for Public Expenditure Control - Reviglio, Franco (IMF Working Papers; Working Paper, 2001)
This paper explains why EMU countries seem unable or unwilling to undertake structural reforms of public expenditure. One of the reasons is political. What public expenditure reforms might be pursued without changing the political system? Without political reforms, technical improvements made to increase budget transparency, such as strengthening budget procedure, integrating accrual into cash accounting, and removing accounting gimmicks, could indirectly affect reforms of public expenditure. Removing gimmicks and helping prevent the emergence of new creative accounting techniques may be a partial substitue for political reforms. Implementation of the Growth and Stability Pact should be dynamically consistent with budgetary transparency. Although other EMU countries resorted as well to budgetary gimmicks to bypass difficult fiscal constraints, the Italian case is used as a reference to clarify these issues. Transparency may help discourage the use of gim micks.